The Ego and the Other: An oppositional relationship (Gibran Khalil Gibran as a model) - Abdul Sada Khalif, Ghanim; Asal Hassan, Essam (Al-Adab Journal, 2020)
There is no doubt that the process of revealing the other does not take place in isolation, for they are two sides of one client, for each of them seeks to achieve and prove its existence at the expense of the other, as there is no existence of the ego except through the other, and since every duality in philosophy has a relationship that connects both parties, so the relationship Antagonism represents a picture of relations that bring together contradictory or contradictory concepts, so we will try to understand the manifestations of the relationship between the ego and the other in opposition to it, according to what was produced by the ideas of the writer Gibran Khalil Gibran in crystallizing these concepts within the limits of the concept of narration.